An Old Story Retold: Loss of G1 Control Defines A Distinct Genomic Subtype of Esophageal Squamous Cell Carcinoma - Qiyan Wang; Jian Bai; Amir Abliz; Ying Liu; Kenan Gong; Jingjing Li; Wenjie Shi; Yaqi Pan; Fangfang Liu; Shujuan Lai; Haijun Yang; Changdong Lu; et al. (Genomics, Proteomics & Bioinformatics, 2015)
Esophageal squamous cell carcinoma (ESCC) has a high mortality rate. To determine the molecular basis of ESCC development, this study sought to identify characteristic genome-wide alterations in ESCC, including exonic mutations and structural alterations. The clinical implications of these genetic alterations were also analyzed. Exome sequencing and verification were performed for nine pairs of ESCC and the matched blood samples, followed by validation with additional samples using Sanger sequencing. Whole-genome SNP arrays were employed to detect copy number alteration (CNA) and loss of heterozygosity (LOH) in 55 cases, including the nine ESCC samples subjected to exome sequencing. A total of 108 non-synonymous somatic mutations (NSSMs) in 102 genes were verified in nine patients. The chromatin modification process was found to be enriched in our gene ontology (GO) analysis. Tumor genomes with TP53 mutations were significantly more unstable than those without TP53 mutations. In terms of the landscape of genomic alterations, deletion of 9p21.3 covering CDKN2A/2B (30.9%), amplification of 11q13.3 covering CCND1 (30.9%), and TP53 point mutation (50.9%) occurred in two-thirds of the cases. These results suggest that the deregulation of the G1 phase during the cell cycle is a key event in ESCC. Furthermore, six minimal common regions were found to be significantly altered in ESCC samples and three of them, 9p21.3, 7p11.2, and 3p12.1, were associated with lymph node metastasis. With the high correlation of TP53 mutation and genomic instability in ESCC, the amplification of CCND1, the deletion of CDKN2A/2B, and the somatic mutation of TP53 appear to play pivotal roles via G1 deregulation and therefore helps to classify this cancer into different genomic subtypes. These findings provide clinical significance that could be useful in future molecular diagnoses and therapeutic targeting.